Mutual coupling reduction in circularly polarized dielectric resonator MIMO antenna - J. Iqbal; U. Illahi; M. I. Sulaiman; M. Alam; MS. Mazliham; L.S Ding (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this article a novel circularly polarized (CP) rectangular dielectric resonator antennas (RDRA’s) array has been designed. A unique conformal feeding strip has been used to excite the RDRA’s having a distance of λ/2. Various techniques are investigated to reduce mutual coupling (MC).  Different formations, comprise of reorientation of the antennas have been employed to suppress MC and to enhance CP bandwidth. By the unique orientation the mutual coupling has been reduced by ~ 14 dB. A broadband circular polarization over a bandwidth of ~ 18.8% in conjunction with an impedance matching bandwidth of ~ 11.3 % has been achieved. The design has been modeled and simulated using computer simulation technology (CST). Two different simulation techniques i.e. finite integration technique (FIT) and Finite element method (FEM) have been used to compute and validate the results respectively. A significant resemblance in results have been observed.